Multicultural education patterns in promoting tolerance among high school students - Sukardi, Joko Sri; Hanum, Farida; Efianingrum, Ariefa (LPMPP Universitas Negeri Yogyakarta, 2025)
The study aims to identify: patterns of multicultural education that foster tolerance in SMA BOPKRI 2, SMA N 3, and SMA Al-Azhar 9 Yogyakarta, and the ideal pattern of multicultural education for developing tolerance in senior high schools. The research employed a qualitative descriptive approach. The research subjects included the principal, vice principal, and subject teachers. Data were collected through observation, interviews, and documentation. The data were analyzed using an interactive model consisting of data collection, data condensation, data presentation, and drawing conclusions. The validity of the data was ensured through triangulation of techniques and sources. The results showed that multicultural education patterns play an important role in developing tolerance in high schools. Specifically: SMA BOPKRI 2 Yogyakarta implemented a multicultural approach in accordance with its mandate, vision, mission, and objectives as a multicultural school; SMA Negeri 3 applied a diversity literacy approach, emphasizing the management of student diversity across ethnic, racial, cultural, linguistic, and religious backgrounds; and SMA Al-Azhar 9 practiced an open and inclusive model of multicultural education aligned with the Islamic principle of Wasathiyah (moderation). The ideal model, which represents the novelty of this research, was conceptualized from the patterns identified in the three schools and is termed the “Moderate Tolerance Empathy Model of Multicultural Education.” This model emphasizes the values of moderate tolerance and empathy as key drivers of mindset, attitudes, and behavior in multicultural senior high schools.